Differences between software retailers from cambridge and braðsov regarding online marketing strategies - Axenia Bianca Boitor; Gabriel Bréatucu (The International Journal of Management Science and Information Technology (IJMSIT), 2013)
This paper presents an analysis and a comparison of the software traders' attitude from Bras,ov and Cambridge cities regarding the online promotion and marketing strategies used on the software market. Two surveys among traders in Cambridge and Bras,ov were performed and the results of the research emphasize a consistent difference between the software traders from Cambridge and those from Bras,ov. A large orientation to the e-commerce was discovered between the software retailers from Cambridge and a very small orientation to the online marketing and sales between the software traders from Bras,ov. At the research took part 13 software companies from Cambridge area and 21 software traders from Bras,ov area.
Keywords: 650; Internet; research; online sales; software